A Case of Prostatic Carcinoma Manifesting as Cutaneous Facial Nodule. (26th February 2018) - Esquivel-Pinto, Israel Antonio; Torres-Alvarez, Bertha; Gómez-Villa, Ramiro Jetzabel; Castanedo-Cázares, Juan Pablo
Abstract : Prostate cancer is the second most frequently diagnosed cancer worldwide and the fifth most common cause of cancer deaths among men. Cutaneous metastasis is an uncommon phenomenon in prostatic cancer, occurring in 0.06–0.3% of cases. Case Presentation. A 56-year-old man presented to our outpatient clinic with a one-month history of a 1.5 cm in diameter, solitary, asymptomatic, purple nodule located on his upper right cheek. After biopsy, prostatic cancer metastasis was diagnosed. Discussion. A literature review revealed 59 articles documenting 71 cases of this diagnosis. The review recorded epidemiological data, including age, duration, morphology, location, and outcome of patients. Conclusions. The skin is an uncommon site for metastasis of prostate cancer, and the review showed that its presence is associated with a poor prognosis (approximately 10 months from diagnosis).